Development and Event-specific Detection of Transgenic Glyphosate-resistant Rice Expressing the G2-EPSPS Gene - Dong, Yufeng; Jin, Xi; Tang, Qiaoling; Zhang, Xin; Yang, Jiangtao; Liu, Xiaojing; Cai, Junfeng; Zhang, Xiaobing; Wang, Xujing; Wang, Zhixing (Frontiers in Plant Science, 2017)
Glyphosate is a widely-used herbicide, due to its broad spectrum, low cost, low toxicity, high efficiency, and nonselective characteristics. Rice farmers rarely use glyphosate as a herbicide, because the crop is sensitive to this chemical. The development of transgenic glyphosate-tolerant rice could greatly improve the economics of rice production. Here, we transformed the Pseudomonas fluorescens G2 5-enolpyruvyl shikimate-3-phosphate synthase (EPSPS) gene G2-EPSPS, which conferred tolerance to glyphosate herbicide into a widely-used japonica rice cultivar, Zhonghua 11 (ZH11), to develop two highly glyphosate-tolerant transgenic rice lines, G2-6 and G2-7, with one exogenous gene integration. Seed germination tests and glyphosate-tolerance assays of plants grown in a greenhouse showed that the two transgenic lines could greatly improve glyphosate tolerance compared with the wild-type; The glyphosate-tolerance field test indicated that both transgenic lines could grow at concentrations of 20 000 ppm glyphosate, which is more than 20-times the recommended concentration in the field. Isolation of the flanking sequence of transgenic rice G2-6 indicated that the 5′-terminal of T-DNA was inserted into chromosome 8 of the rice genome. An event-specific PCR test system was established and the limit of detection of the primers reached 5 copies. Overall, the G2-EPSPS gene significantly improved glyphosate-tolerance in transgenic rice; furthermore, it is a useful candidate gene for the future development of commercial transgenic rice.